Genotypic and phenotypic characterization of thermo-sensitive genic male sterile (TGMS) rice lines using simple sequence repeat (SSR) markers and population structure analysis - B Nagendra Naidu; Manonmani Swaminathan; Pushpam Ramamoorthy; Kumaresan Dharmalingam; Raveendran Muthurajan; Selvi Duraisamy; Nivedha Rakkimuthu; Abirami Subramanian; Rithesh Natarajan; Bonipas Antony John (PeerJ)
Thermo-sensitive genic male sterile (TGMS) lines in rice are crucial for hybrid breeding, enhancing genetic diversity by eliminating the need for manual emasculation and restorer genes. These lines induce sterility at high temperatures and restore fertility at low temperatures, in contrast to cytoplasmic male sterility (CMS) systems that require specific restorative genes. This temperature-sensitive mechanism allows for greater flexibility in pairing parent lines, increasing genetic diversity and enabling recombination of beneficial traits in hybrids. A randomized block design (RBD) with three replications was employed for the evaluation of these TGMS rice lines. This study investigates the molecular diversity and genetic variability among TGMS rice lines. Traits such as single plant yield, grains per panicle, glume angle, and pollen fertility showed significant phenotypic and genotypic variation, indicated by high coefficients of variation (PCV and GCV), heritability estimates, and genetic advance as a percentage of mean (GAM). These results highlight substantial genetic variation and selection potential. Euclidean distance matrix analysis of morphological data revealed notable genetic differences. TNAU 137S 1 and TNAU 137S 2 were the most genetically similar, while TNAU 112S and TNAU 114S showed the greatest divergence. Principal component analysis (PCA) revealed distinct genetic profiles among lines such as TNAU 136S, TNAU 113S, TNAU 142S, and TNAU 126S, important for hybrid development. Molecular diversity analysis using simple sequence repeat (SSR) markers identified 90 alleles and eight genetic clusters. Bayesian analysis further confirmed two major subpopulations with significant genetic divergence. These findings support the selective use of parent lines for hybrid rice breeding.